Perbedaan Kemampuan Lansia dalam Membina Hubungan Sosial yang Intim Berdasarkan Ketertibatannya dalam Dunia Kerja dan Tingkat Pendidikan - Sri Respati Andamari & Bimo Walgito (LPPM Universitas Proklamasi 45, 2010)
Objective of tliis research was to determine whether elderly educational level and their participation in labor force influenced their ability to maintain intimate social relationship. To translate that objective, vre divided elderly samples into 2 groups based on their participation in labor force, and then those elderly were asked about their ability in maintain intimate social relationship. The next similar strategy was also applied but the elderly sample was divided into 2 groups based on their educational lcvcL The activity theory was applied in order to answer 2 hypotheses. The first hypothesis was that there would be a different ability on maintaining intimate social relationship between the active and inactive elderly in labor participation. The active elderly would have more ability to maintain intimate social relationship than the inactive elderly. The second hypothesis was that there would be a different ability to maintain intimate social relationship between the elderly with high and low educational levels. Elderly with high educational level would have more ability to maintain intimate social relationship than the less educated elderly. It was 120 elderly aged 65-80 years old participated in this research. The 2 ways analysis variance computation revealed that there was no differentiation between the active and inactive elderly in maintaining social relationship. It was also revealed that there was different ability in maintaining intimate relationship between the elderly attained high and low educational levels. Apparendy having more educational attainment would surely address higher ability in maintaining intimate social relationship. Several arguments on answering the inability of active theory to answer the first hypotheses were discussed below.